PEMANFAATAN TEKNOLOGI BLOCKCHAIN UNTUK RANTAI PASOKAN PERTANIAN YANG TRANSPARAN DAN BERKELANJUTAN - Sigit Sugiardi (Prosiding Seminar Nasional Indonesia, 2025)
The use of blockchain technology in the agricultural supply chain offers innovative solutions to address issues of transparency, data security, and distribution efficiency, which have long been major challenges for the agricultural sector. With its decentralised recording system and smart contract features, blockchain is able to permanently record every transaction and product movement in a transparent manner that can be verified by all stakeholders. This not only enhances consumer confidence in the origin and quality of products but also accelerates distribution processes and reduces the risk of counterfeiting and disputes in transactions. However, the implementation of blockchain in the agricultural sector still faces challenges such as the need for digital infrastructure, technological literacy, and cross-sector collaboration. With the right policies and synergy between the government, businesses, and farmers, blockchain technology has great potential to build a more transparent, efficient, and sustainable agricultural supply chain in the future.